Ventral tegmental area dysfunction affects decision-making in patients with myotonic dystrophy type-1. (July 2020) - Serra, Laura; Scocchia, Marta; Meola, Giovanni; D'Amelio, Marcello; Bruschini, Michela; Silvestri, Gabriella; Petrucci, Antonio; Di Domenico, Carlotta; Caltagirone, Carlo; Koch, Giacomo; Cercignani, Mara; Petrosini, Laura; et al.
Abstract: The clinical manifestations of Myotonic Dystrophy type-1 (DM1) are associated with a complex mixture of multisystem features including cognitive dysfunctions that strongly impact on patients' social and occupational functioning. Decision making, a function controlled by dopaminergic circuitry, is critical for succeeding in one's social and professional life. We tested here the hypothesis that altered connectivity of the ventral tegmental area (VTA), one of the major sources of diffuse dopaminergic projections in the brain, might account for some higher-level dysfunctions observed in patients with DM1. In this case–control study, we recruited 31 patients with DM1 and 26 healthy controls who underwent the IOWA Gambling task and resting-state functional MRI (RS-fMRI) at 3T. Functional connectivity of the VTA was assessed using RS-fMRI. VTA connectivity was compared between 25 DM1 patients and all the controls, and the presence of associations between VTA connectivity and IOWA Gambling task performance was also investigated. DM1 patients performed significantly worse than controls at the IOWA Gambling task. A significant increase of functional connectivity was observed between VTA and the left supramarginal and superior temporal gyri in DM1 patients. Patients' IOWA Gambling task net-scores were strictly associated with VTA-driven functional connectivity in the bilateral supplementary motor area and right precentral gyrus. This study demonstrates a prominent deficit of decision-making in patients with DM1. It might be related to increased connectivity between VTA and brain areas critically involved in the reward/punishment system and social cognition. These findings indicate that dopaminergic function is a potential target for pharmacological and non-pharmacological interventions in DM1.